Effectiveness of Adapted Taekwondo, Multi-Component Training and Walking Exercise on Health Status in Independent Older Women: Study Protocol for a Randomized Controlled Trial (Tkd & Aging Project) - Herrera-Valenzuela, T (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This study protocol aims to analyze and compare the effects of an adapted taekwondo program with respect to multi-component training and walking exercise on health status in independent older women. Secondarily, we analyze the variability of the inter-individual response and compare it according to the designated training system. The sample will consist of 64 women between 60 and 65 years, randomly assigned to experimental group 1 (n = 16; adapted taekwondo), experimental group 2 (n = 16; multi-component training), experimental group 3 (n = 16, walking exercise) or control group (n = 16; no intervention). The experimental groups will perform the designated training for three sessions (60 min per session) per week over 16-weeks, while the control group will not receive any treatment. The main outcome will provide information about (i) blood pressure, (ii) lipid profile, (iii) frequency of food consumption, (iv) body composition, (v) cognitive status, (vi) brain activity, (vii) health-related quality of life (HRQoL) and (viii) physical-functional fitness. Our hypothesis indicates that adapted taekwondo produces more significant effects and greater inter-individual responses in cognitive status, brain activity, HRQoL, and postural balance than the others training methods. If this intervention proves effective, it could be an alternative for older women. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.